Evangelization on Social Media: Generalities and Proposals for the Future - Mora Núñez, Nestor (2021)
Evangelization in social networks is a reality and, at the same time, a challenge for the Church of the 21st century. Virtual social networks have replaced, in many aspects, the traditional evangelization forums and spaces. Similarly, the experience of faith is moving its center of gravity from face-to-face to virtuality. This article presents a series of bases necessary to understand how to start evangelization using high-tech tools and the necessary creativity to do so.